2023
DOI: 10.3390/ijms24065131
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic Peptides: It Is Time for Guided Therapeutic Strategies Based on Their Molecular Mechanisms

Abstract: Natriuretic peptides (NPs) are the principal expression products of the endocrine function of the heart. They exert several beneficial effects, mostly mediated through guanylate cyclase-A coupled receptors, including natriuresis, diuresis, vasorelaxation, blood volume and blood pressure reduction, and regulation of electrolyte homeostasis. As a result of their biological functions, NPs counterbalance neurohormonal dysregulation in heart failure and other cardiovascular diseases. NPs have been also validated as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…Its diverse physiological impacts on the cardiovascular and renal systems, including natriuresis, diuresis, vasorelaxation, reduction of blood volume, and inhibition of the renin-angiotensin-aldosterone system (RAAS), have been elucidated [ 46 ]. The modulation of ANP levels and activity has recently become a focal point in clinical research, presenting promising therapeutic avenues for heart failure [ 46 , 47 ]. Our findings highlight the significant role of ANP upregulation and its influence on balancing ER stress and autophagy in the cardiac protective effects of liraglutide administration.…”
Section: Discussionmentioning
confidence: 99%
“…Its diverse physiological impacts on the cardiovascular and renal systems, including natriuresis, diuresis, vasorelaxation, reduction of blood volume, and inhibition of the renin-angiotensin-aldosterone system (RAAS), have been elucidated [ 46 ]. The modulation of ANP levels and activity has recently become a focal point in clinical research, presenting promising therapeutic avenues for heart failure [ 46 , 47 ]. Our findings highlight the significant role of ANP upregulation and its influence on balancing ER stress and autophagy in the cardiac protective effects of liraglutide administration.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of NPs in HFpEF is controversial, and their levels should be carefully evaluated on a case-by-case basis and corroborated by other imaging parameters [ 32 ]. Limited data are available regarding NPs in patients with HFpEF [ 33 ], and recent studies suggested that elevated circulating levels of NPs are strong predictors of adverse and fatal CV events in these patients [ 34 , 35 ].…”
Section: Multimodality Imaging and Natriuretic Peptidementioning
confidence: 99%
“…Natriuretic peptides: Natriuretic peptides are hormones secreted from the heart to promote Na + excretion in the kidneys. Currently, there are three known peptides in the natriuretic peptides family: atrial natriuretic peptide (ANP), B-type natriuretic peptide (BNP), and C-type natriuretic peptide (CNP) [84]. ANP is hypoxia-responsive and its circulating levels are increased by decreased clearance due to downregulation of the natriuretic peptide receptor-C in hypoxia [85].…”
Section: Potential Mechanisms Regulating Renin Under Hypoxiamentioning
confidence: 99%